Cobalt oxide functionalized nanoporous carbon electrodes and their excellent supercapacitive performance1. Issue 18 (5th March 2015) - Dhawale, Dattatray S.; Mane, Gurudas P.; Joseph, Stalin; Talapaneni, Siddulu N.; Anand, Chokkalingam; Mano, Ajayan; Aldeyab, Salem S.; Lakhi, Kripal S.; Vinu, Ajayan
<x xml:space="preserve">Abstract</x> Nanoporous carbon (CMK-3-150) functionalized with different amounts of cobalt oxide (CoO) nanoparticles was synthesized by an incipient wetness impregnation technique for supercapacitor application.